2020
DOI: 10.21608/ejchem.2019.7264.1593
|View full text |Cite
|
Sign up to set email alerts
|

Lower Cost and Higher UV-Absorption of Polyvinyl Alcohol/ Silica Nanocomposites For Potential Applications

Abstract: F ilms of (polyvinyl alcohol-silicon dioxide) nanocomposites were prepared for UV-shielding with low cost, low weight and excellent anti-UV properties. Studying the structural and optical properties of PVA/SiO2 nanocomposites have been investigated. The experimental results showed that the absorbance (A), absorption coefficient (α), extinction coefficient (K), refractive index (n), real (ε1) and imaginary (ε2) parts of dielectric constants and optical conductivity (σop) of PVA are increased with increasing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…Figures 7 and 8 show the energy band gap of nanocomposites. From the values of the absorption coefficient, it can be concluded that the nanocomposites have indirect energy band gap, it is decrease with increasing the ZnCoFe 2 O 4 nanoparticles, this behavior is due to the creation of levels in the energy gap [22][23][24][25].…”
Section: Resultsmentioning
confidence: 99%
“…Figures 7 and 8 show the energy band gap of nanocomposites. From the values of the absorption coefficient, it can be concluded that the nanocomposites have indirect energy band gap, it is decrease with increasing the ZnCoFe 2 O 4 nanoparticles, this behavior is due to the creation of levels in the energy gap [22][23][24][25].…”
Section: Resultsmentioning
confidence: 99%
“…The optical conductivity of blend rises with the increase in MnO2 NPs ratio and photon energy. The rise in optical conductivity as MnO2 NPs ratio increase due to reduce the energy gap [27][28]. [29,30].…”
Section: A D C Bmentioning
confidence: 99%
“…Absorptio band gap of PEO decreases with adding of NiO, this behavior due to increase of the localized level in energy gap [22][23][24][25][26][27][28][29][30], which make it suitable in many optoelectronics applications.…”
Section: Wavelength(nm)mentioning
confidence: 99%